2010
DOI: 10.1016/j.jmacro.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Inflation persistence in the Franc zone: Evidence from disaggregated prices

Abstract: In sub-Saharan Africa, where inflation persistence is likely to have deleterious welfare consequences, little attempt has been made to study this phenomenon. Using data over 1989:11-2002:09, this paper investigates persistence in disaggregated (food and non-food) inflation for thirteen Communauté Financière Africaine (CFA) member states using fractional integration (FI) methods. The results show that both inflation series are characterized by mean-reversion and finite variance, however it also exposes some asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Coleman (2010) investigates the incidence of inflation persistence in the African CFA Franc zone for a two broad sectors i.e., food and nonfood.…”
mentioning
confidence: 99%
“…Coleman (2010) investigates the incidence of inflation persistence in the African CFA Franc zone for a two broad sectors i.e., food and nonfood.…”
mentioning
confidence: 99%
“…As highlighted by Coleman (2010), inflation persistence could be present in Chad. In fact, the effect of rainfall, public spending, nominal effective exchange rate, and foreign prices on inflation could last after the first, second or third quarter, reflecting second round effects.…”
Section: Inflation Modelling In Chad 3127mentioning
confidence: 96%
“…For the GCC countries, Kandil and Morsy (2009) concluded that inflation in trading partners as well as credit and aggregate spending explain inflation. Coleman (2010) analysed inflation persistence in 13 Communaute´Financie`re Africaine (CFA) member states and highlighted that inflation is persistent in Chad, Cote d'Ivoire and Niger. 1 The empirical strategy in this article combines three estimation methods: the Vector Error Correction Model (VECM), the single-equation model, and the Structural Vector Autoregression (SVAR) model.…”
Section: Introductionmentioning
confidence: 99%
“…inflation, growth, per capita and currency union. (Coleman, 2010;Harvey & Cushing, 2015)The common stock of macroeconomic policies more in under developing countries, which makes a common strategic policy for individual states.…”
Section: Literaturementioning
confidence: 99%